PENDAPATAN NELAYAN PANCING ULUR DI KELURAHAN LESANE KABUPATEN MALUKU TENGAH - Deva Syahdilla Harun; Saiful Saiful; Angela Ruban (Universitas Pattimura, 2023)
Fishing activities using Hand Rods in Lesane Village, Central Maluku Regency are the main source of income for the community. This research was carried out in May – June 2022, the location of this research was the hand line fishing business in Lesane Village, Central Maluku Regency. This research aims to analyze the income level of traditional fishermen in Lesan Village, Central Maluku Regency. The basic research method refers to the descriptive research method where research is carried out to determine the value of each variable, whether one or more independent variables without making relationships or comparisons with other variables. To analyze income data in the hand line fishing business, a quantitative data analysis method is used. The income of Lesane fishermen from this profit-sharing system can be explained simply, namely the total revenue from production minus production costs during fishing activities, which then results in the income of Lesane fishermen being obtained from agreed percentage or profit sharing, mathematically using the formula π = TR-TC. The results of this research show that the total income of traditional handline fishermen in Lesane Village, Central Maluku Regency is IDR 93,723,757. The highest income for fishermen is IDR 16,951,754. and the lowest is IDR 12,801,054. with the average income of hand-line fishermen in Lesane Village, Central Maluku Regency, namely IDR 15,620,626. The income of hand-line fishermen in Lesane Village, Central Maluku Regency is influenced by capital, labor, business experience and season.